PENERAPAN STRATEGI BISNIS PADA USAHA FASHION KIAPIX - Afifah, Husna; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify the appropriate application of business strategy at Kiapix fashion business in Madiun regency and to identify its marketing strategy based on SWOT analysis. This qualitative descriptive study was started by identifying and analyzing internal and external environmental factors that influence the business, followed by determining the correct strategy based on the alternatives of strategy formulation produced from analyses on IFE Matrix, EFE Matrix, SWOT (Strength, Weakness, Opportunity, and Threat), and IE Matrix. This study finds that the internal environmental factor of Kiapix consists of five opportunities and five threats. The alternative of strategy produced from SWOT analysis and IE Matrix is grow and build. Based on this strategy, the business needs new target market and it should match the company’s product. Furthermore, it needs to make a new product packaging, make a better and clearer distribution channels, make a different price policy, and make new market segment.